2005
DOI: 10.1242/jcs.01737
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of neutrophil cyclooxygenase-2 by adenosine: an early anti-inflammatory signal

Abstract: Neutrophils, which are often the first to migrate at inflamed sites, can generate leukotriene B4 from the 5-lipoxygenase pathway and prostaglandin E2 through the inducible cyclooxygenase-2 pathway. Adenosine, an endogenous autacoid with several anti-inflammatory properties, blocks the synthesis of leukotriene B4 while it potentiates the cyclooxygenase-2 pathway in fMLP-treated neutrophils, following activation of the A2A receptor. Using the murine air pouch model of inflammation, we observed that inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 60 publications
5
46
0
1
Order By: Relevance
“…It has been described that GPER activation promotes adenylate cyclase activation (8). In addition, stimuli known to elevate intracellular cAMP levels, such as PGE 2 , adenosine, and isoproterenol, positively modulate the PTGS2 expression (63)(64)(65). In support of this mechanism, we observed that G1 promoted the phosphorylation of CREB and that the induction of PTGS2 and the phosphorylation of CREB were both mimicked by dbcAMP, a cell-permeant cAMP analog.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been described that GPER activation promotes adenylate cyclase activation (8). In addition, stimuli known to elevate intracellular cAMP levels, such as PGE 2 , adenosine, and isoproterenol, positively modulate the PTGS2 expression (63)(64)(65). In support of this mechanism, we observed that G1 promoted the phosphorylation of CREB and that the induction of PTGS2 and the phosphorylation of CREB were both mimicked by dbcAMP, a cell-permeant cAMP analog.…”
Section: Discussionsupporting
confidence: 78%
“…No symbol or "ns" means not significant. consequence of the complex regulatory mechanisms of CREB activation/deactivation (63). Thus, the activation of the protein phosphatase involved in the dephosphorylation of CREB also depends on PKA activity (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…7B) or t=4 h (data not shown). Moreover, activation of the A 2A adenosine receptor, which potentiates COX-2 expression in these conditions [13,30], also failed to significantly alter the expression of mPGES-1 (Fig. 7C).…”
Section: Constitutive Expression Of Mpge Synthase-1 In Neutrophilsmentioning
confidence: 91%
“…Reverse-transcription and real-time PCR were performed essentially as described in [30]. Briefly, first strand cDNA synthesis was performed using 1 μg of total RNA with Superscript II (Invitrogen Lifetechnology, Carlsbad, CA, USA) in recommended conditions, using 500 ng of random hexamers.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…D'une part, il bloque la libération de l'acide arachi donique de la membrane plasmique et la translocation de [Adénosine] la 5-LO vers la membrane nucléaire, empêchant ainsi la synthèse de LTB 4 [24]. D'autre part, il potentialise l'expression de la COX-2 (transcrit et protéine), in vitro et in vivo [25,26] dans les PN neutrophiles infiltrés dans la poche après une injection de LPS. L'activation du récepteur A 2A peut également inhiber la sécrétion de matrix metalloproteinases (MMP), protéines qui participent à la dégradation matricielle, par exemple MMP9 [29].…”
Section: Polynucléaires Neutrophiles Et Résolution Du Processus Inflaunclassified